Increased lipid peroxidation, depleted non‐enzymatic antioxidant, and variability in trace elements concentration in serum are correlated with Bangladeshi end‐stage renal disease population. Issue 3 (6th August 2021) - Hossain, Md. Shohel; Amin, Mohammad Nurul; Das, Abhijit; Khan, A. K. M. Jahirul Hossain; Sohel, Md; Ahmed, Jamiuddin; Islam, Md. Monirul; Hossain, Md. Shahadat; Rahman, Md. Masudur; Nesa, Mst. Luthfun; Islam, Mohammad Safiqul
Abstract: Introduction: End‐stage renal disease (ESRD) is an abnormality where the kidneys are not usually working. This case‐control study was planned to determine the extent of serum lipid peroxidation, non‐enzymatic antioxidant (vitamin c), and trace elements in 50 patients with ESRD as cases and 50 normal healthy individuals as controls. Methods: Determination of lipid peroxidation was carried out by ascertaining concentration of malondialdehyde (MDA) and vitamin C in serum using UV spectrophotometry whereas atomic absorption spectroscopy was used for trace elements estimation. The statistical analysis was conducted via the independent t ‐test samples and Pearson correlation test. Results: The blood serum study has shown substantially higher MDA values than the control level and lowers vitamin C levels in the patient population ( P  < .001). A negative correlation was found between the vitamin C in serum with BMI and MDA for both patients ( r  = −0.017 and r  = −0.132, respectively) and the control group ( r  = −0.014 and r  = −0.229, respectively) after Pearson's correlation analysis. Regarding trace elements, significantly ( P  < .001) lower concentrations of zinc, copper, and manganese were found in the patient group than control subjects. Inter‐element‐relationship established a strong positive harmonization between these studied elements in both the cases of patients and control subjects. Conclusion: Our results indicate strong associations of the pathogenesis of ESRD with depleted non‐enzymatic antioxidant, increased lipid peroxidation, and inconsistency in trace elements concentration in serum, which may provide a prognostic tool for the treatment of this concerning the disease.